Household Saving Behaviour in New Zealand: Why do Cohorts Behave Differently? - Grant M Scobie; John K Gibson (New Zealand Government, The Treasury, 2003)
The aim of this paper is to add to the understanding of saving decisions by households. The saving behaviour of households is found to differ depending on the birth cohort of the household head. This paper seeks to explain why this pattern might exist. It is based on an analysis of synthetic cohorts derived from unit record data taken from the Household Economic Survey (HES) for the March years 1984 to 1998. The need to use synthetic cohorts arises as the HES is not a longitudinal panel survey, but rather a time series of independent cross-sectional samples. We use a range of regression models to separate out the effect of age, birth-year cohort and year on saving rates. The typical saving rates for the cohorts born between 1920 and 1939 are found to be significantly lower relative to the younger and older cohorts studied. This pattern of cohort effects is robust to the inclusion of conditioning variables; to the trimming from the sample of households with either negative or very large ratios of savings to consumption, and to different definitions of saving. Some exploratory investigation supports the hypothesis that changes in the economic and policy environment help explain the different saving behaviour of different birth cohorts. Tentative results suggest that more ?favourable environments are associated with lower rates of lifetime saving.
Keywords: E21; J26; 330; Household saving rates; cohort effects; New Zealand; economic and social policies